Sodobni postopki barvanja in barva: Navodila za vaje - Fakin, Darinka; Gorgieva, Selestina; Ojstršek, Alenka (2020)
Advances Dyeing Processes and Colour: Exercise Instructions. Exercises “Advances dyeing processes and colour” deal with the systematics and nomenclature of dyes, the physical chemistry of dyeing processes and the use of advanced materials and techniques in the dyeing processes. Most of them are dedicated to special processes that enable a modern way of dyeing and, at the same time, achieve a higher level of quality in terms of ecology and (multi)functional properties of materials, and dyeing with natural dyes. We specifically study the dyeing under conditions of supercritical CO2, dyeing with ultrasound or plasma pre-treatment, and dyeing with functional dyes. Special properties could be achieved with this type of dyes such as: thermochromism, photochromism, electrochromism, solvatochromism and other special effects.
Keywords: Colour; natural dyes; functional dyes; ultrasound; advanced materials